Analysis the level of Efficiency of Sharia Commercial Bank and Sharia Business Unit in Indonesia with Data Envelopment Analysis Method - Aziz, Roikhan Mochamad; Amanda, Dita Nur (Jurnal Organisasi dan Manajemen, 2021)
This research has the purpose to measure efficiency and analyze the efficiency comparison between Sharia Commercial Bank (BUS) and Sharia Bussines Unit (UUS) in Indonesia and compare the efficiency during the period 2008-2013. There are 10 Islamic banks which are used as samples of this research consisting of 3 Sharia Commercial Bank (BUS) and 7 Sharia Business Unit (UUS) that were chosen by purposive sampling. Efficiency measurements in this research using Data Envelopment Analysis (DEA). To determine differences in efficiency between Sharia Commercial Bank (BUS) and Sharia Bussines Unit (UUS), this study uses a different test parametric independent sample t-test. The result of this research showed that there is no significant difference between the efficiency of Sharia Commercial Bank (BUS) and Sharia Bussines Unit (UUS), during the period of 2008-2013 with possible intervention t value (-0.429) < t table (2.002) and probability value =0.000.